A study of association of ocular biometric parameters with various grades of diabetic macular edema and severity of diabetic retinopathy - Prerna Kataria; Neha K. Sethi; Gagandeep K. Brar; Navchint Singh; Manisha Bagga; Charu Chadha (Journal of Family Medicine and Primary Care)
Context: This study was carried out to evaluate the association of ocular biometric parameters with different grades of diabetic macular edema (DME) and severity of diabetic retinopathy (DR). Four parameters i.e., Spherical equivalent (S.E), Corneal curvature (CC), Axial length (AL), and Anterior chamber Depth (ACD), were evaluated. Aims: Our aim was to study the association of ocular biometric parameters with diabetic retinopathy (DR) of varying severity and grades of diabetic macular edema (DME). Settings and Design: This cross-sectional descriptive study was done at the tertiary care hospital over a period of 18 months. Methods and Material: The study included 242 eyes of 200 eligible patients with a history of diabetes mellitus type 2 having various grades of non-proliferative Diabetic retinopathy (NPDR) (graded according to the AAO 2012 Classification system). Out of 242 eyes, 58 eyes were classified as having Diabetic macular edema (DME) (confirmed on OCT through drcr.net study). S.E, CC, AL, and ACD were calculated in each eye, and association was studied with DME and severity of DR. Statistical Analysis Used: ANOVA test and t-test were performed. Results: In our study, we found structural components, i.e., AL and ACD being a protective factor for diabetic macular edema. A significant association was observed between AL and different grades of DR. Conclusion: We conclude that longer AL may be a protective factor against severe grades of NPDR. Also, a significant association of ACD with DME was an exclusive finding.